(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2023)
The Lithiotis facies represents an Early Jurassic global bioevent characterized by a remarkable spread of gregarious bivalves, which produced large sedimentary bodies in tropical shallow-water marine environments. The most peculiar and common genera Lithiotis, Cochlearites and Lithioperna, with aberrant and extremely elongated or strongly flattened shells, have been studied since the second half of the nineteenth century. Despite numerous systematic studies, their phylogenetic relationship with the other bivalve families is still uncertain. The Lithiotis facies yields other bivalve genera, among which a large multivincular mytiloid, provisionally determined as Isognomon (Mytiloperna) sp. ind. or Mytiloperna sp., is recorded in the literature. This taxon is here studied from a systematic point of view to clarify its taxonomic position and solve the open nomenclature adopted in the past. Here, we propose a new genus Pachygervillia and a new species Pachygervillia anguillaensis. The stratotype is located in the lower part of the Rotzo Formation (Calcari Grigi Group, Lower Jurassic), while the type locality is in the Lessini Mountains (Verona Province, Trento Platform, Southern Alps). This new species is characterized by a thick aragonitic inner shell layer with a fibrous, irregular, spherulitic, prismatic microstructure combined with a nacreous middle layer, both also occurring in species of the genera Lithiotis and Cochlearites of the family Plicatostylidae. This microstructural layering is here proposed as the main taxonomic character of the family, which is here emended and divided into the following two subfamilies: Plicatostylinae, yielding Lithiotis and Cochlearites with stick-like shells, and Pachygervilliinae nov. subfam., yielding Gervilleioperna, Lithioperna, Pachygervillia n. gen., and Pachyperna, previously placed within the subfamily Isognomoninae.